EFEKTIVITAS PEMBERIAN COOKIES TAPE KETAN HITAM DAN EDUKASI GIZI TERHADAP PENURUNAN BERAT BADAN PADA REMAJA GEMUK - Rahmat, Mamat; Gumilar, Mulus; Dewi, Maryati (Media Penelitian dan Pengembangan Kesehatan, 2023)
Black glutinous tape contains anthocyanins and has antioxidant activity as well as fiber. Consumption of black glutinous tape at least >11.5grams a day can prevent the occurrence of metabolic syndrome. One of the components of metabolic syndrome is the accumulation of fat around the waist (central obesity). The study aimed to determine the effectiveness of giving black glutinous rice tape cookies and nutritional education on weight loss in obese adolescents. The research design used quasi-experiments before and post-test two groups, by comparing the change in body weight between subjects who were given black tape cookies and subjects who were given nutrition education. The research was conducted in August-September 2017 at SMAN 2 and 3 Cimahi. The population is all students who are obese based on the BMI/U indicator of a Z score value of>+1.  The minimum sample size in each group was 21. The study showed that there was an average weight decrease in the group given black glutinous rice tape cookies (0.53+1.41kg) and in the group given nutrition education (0.43+1.40kg). Based on statistical tests, there was no difference in weight before and after the intervention (p>0.05). Giving black glutinous rice tape cookies and providing nutrition education for one month to obese teenagers can lead to weight loss, but this has not been statistically proven. Further research is needed on the provision of sticky rice tape cookies with various weights and with a longer period of time so that the impact of weight loss on obese teenagers can be observed.